Self-Inflicted Hyperkalemia: A Case Report. (29th May 2012) - Lisenbee, Nathaniel; Desai, Bobby; Falgiani, Michael
Abstract : We present a case of a potentially lethal ingestion of potassium pills. After presentation, we briefly review the epidemiology and pathology of hyperkalemia.